HUMAN-ORIENTED QUALITY MANAGEMENT SYSTEM OF ENTERPRISE: CONTROL OF NON-CONFORMING PRODUCT AND UTILIZATION - Vyacheslav Feoktistovich Bezyazychny; Maria Evgenyevna Ilyina (Advanced Engineering Research)
The research objective is efficiency increase of the development, estimation, and improvement of quality management systems (QMS) of the machine-building enterprises. The existing classifications and operation algorithms of the QMS basic types allow optimizing the processes of product improvement, and the quality of life of the system participants improvement. The presented model algorithm reflects all possible action variants directed on the improvement and the most effective use of non-conforming product. The algorithm respects the interests of both consumer and manufacturer, and it can be applied at different product life cycle stages. The data analysis of the non-conforming product control results allows improving the applied models and developing the optimization techniques. Thus, there appear options for using products inconsistent with requirements for the initial or near it appointment. Consequently, they would not be completely processed.